Pemeriksaan Kesehatan Lansia di Posyandu Mawar Pajang Surakarta - Siti Sarifah; Anggi Luckita Sari (Jurnal Pengabdian Kepada Masyarakat, 2024)
Elderly health checks are an important part of efforts to maintain quality of life and prevent degenerative diseases that often occur in old age. This program is implemented at Posyandu Mawar, Pajang, Surakarta, with the aim of detecting early health conditions of the elderly and providing education related to healthy lifestyles. The activities include checking blood pressure, blood sugar, body mass index (BMI), and health consultations aimed at maintaining the overall physical condition of the elderly. The results of the examination showed that most of the elderly who participated in this program experienced mild to moderate hypertension and increased blood sugar levels. This program also succeeded in increasing elderly awareness of the importance of routine health checks and healthy lifestyle changes, including more regular diet and physical activity. As a preventive measure, periodic health checks at Posyandu are expected to reduce the risk of degenerative diseases and improve the overall quality of life of the elderly. Therefore, this health check program needs to be continuously supported and implemented sustainably